2005
DOI: 10.1111/j.1471-8286.2005.01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and PCR multiplexing of polymorphic microsatellite loci in cashew (Anacardium occidentale L.) and their cross‐species utilization

Abstract: Cashew ( Anacardium occidentale L.) is the most economically important tropical nut crop in the world, and yet there are no sequence tagged site (STS) markers available for its study. Here we use an automated, high-throughput system to isolate cashew microsatellites from a non-enriched genomic library blotted onto membranes at high density for screening. Sixty-five sequences contained a microsatellite array, of which 21 proved polymorphic among a closely related seed garden population of 49 genotypes. Twelve m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 9 publications
3
43
0
1
Order By: Relevance
“…In collaboration with the Leibniz Institute of Plant Genetics and Crop Plant Research (IPK), Gatersleben, Germany, one hundred and eighty-seven (187) cashew accessions from different populations are being evaluated using 10 simple sequence repeats (SSR) markers (Croxford et al, 2006) (Table 5 ). An overview of the phenogram derived from the molecular data showed that eight (8) of the ten (10) microsatellite loci except, mAoR2 and mAoR47 were polymorphic (Fig.…”
Section: Microsatellite Analysis Reveals Genetic Redundancy In Nigerimentioning
confidence: 99%
“…In collaboration with the Leibniz Institute of Plant Genetics and Crop Plant Research (IPK), Gatersleben, Germany, one hundred and eighty-seven (187) cashew accessions from different populations are being evaluated using 10 simple sequence repeats (SSR) markers (Croxford et al, 2006) (Table 5 ). An overview of the phenogram derived from the molecular data showed that eight (8) of the ten (10) microsatellite loci except, mAoR2 and mAoR47 were polymorphic (Fig.…”
Section: Microsatellite Analysis Reveals Genetic Redundancy In Nigerimentioning
confidence: 99%
“…Furthermore, none of the pairs of loci showed linkage disequilibrium in A. humile. However, the transferred microsatellite markers are suitable for studies of kinship, in accordance with the results observed in A. occidentale, in which all loci showed independent behavior (Croxford et al, 2006). Collevatti et al (1999) have suggested that the high combined probability of paternity exclusion (0.99) found for SSR markers developed for Caryocar brasiliense enables detailed studies of kinship in natural populations, even without a priori knowledge of maternity and paternity of the individuals.…”
Section: Characterization Of the Polymorphic Ssr Locimentioning
confidence: 59%
“…This maximum number was found at locus mAoR17 (Croxford et al, 2006), which showed 4 alleles in A. humile. However, among the other markers analyzed in this study, the number of alleles per locus was higher in A. humile than in A. occidentale.…”
Section: Characterization Of the Polymorphic Ssr Locimentioning
confidence: 93%
See 2 more Smart Citations